Ferritin has an important immune function in the ark shell Scapharca broughtonii. (June 2016) - Zheng, Libing; Liu, Zhihong; Wu, Biao; Dong, Yinghui; Zhou, Liqing; Tian, Jiteng; Sun, Xiujun; Yang, Aiguo
Abstract: Ferritin, the principle cytosolic iron storage protein in the majority of living organisms, has important roles during immune process in invertebrates. Detailed information about ferritin in the ark shell Scapharca broughtonii, however, has been very limited. In this study, full-length ferritin (termed SbFer ) was cloned by the rapid amplication of cDNA ends (RACE) method based upon the sequence from the transcriptome library. The cDNA contained a 182 bp 5′-untranslated region, a 519 bp open reading frame encoding a polypeptide of 172 amino acids, a 229 bp 3′-untranslated region, and three introns (902, 373 and 402 bp) embedded in four exons. There was an iron response element (IRE) in the 5′-untranslated region. The deduced amino acid sequence of SbFer possessed many characteristics of vertebrate H type ferritin, shared 63%–91% identity with mollusks and greater identity with vertebrate H type ferritin compared to the L type. The SbFer gene expression pattern examined by quantitative real-time PCR showed ferritin mRNA was expressed in all ark shell tissues examined. The highest levels of expression were found in hemocytes with decreasing levels of expression in foot, mantle, gill, adductor muscle and hepatopancreas. A challenge with Vibrio anguillarum resulted in time-dependent significant upregulation of SbFer mRNA, indicating SbFer participated actively in the bacterial defense process. Further analysis of the antibacterial activity indicated recombinant SbFer could function as an immune antibacterial agent to both Gram-positive and Gram-negative bacteria. Taken together, these results suggested strongly that ferritin of the ark shell is involved in immune defense against microbial infection and it is a constitutive and inducible acute-phase protein. Highlights: Full length of ferritin gene in S. broughtonii ( SbFer ) is cloned. SbFer is involved in the acute phase response. Recombinant protein SbFer owns strong antibacterial activity.